Strategies to overcome foaming and wall-growth during the cultivation of Morinda elliptica cell suspension culture in a stirred-tank bioreactor - Abdullah, Mohd Azmuddin; Ariff, Arbakariya; Mahmood, Maziah; Ali, Abdul Manaf; Lajis, Md Nordin (Springer, 2000)
Strategies to overcome foaming and wall-growth during the cultivation of Morinda elliptica (Rubiaceae) cell suspension cultures in a stirred-tank bioreactor are described. Of all the strategies applied, only bubble-free aeration was successful in eliminating foaming by 100%. Despite the foaming effect of around 40% in G medium strategy with 0.012% (v/v) antifoam, the maximum dry cell weight attained (19.2 g 1-1) and anthraquinone (AQ) content (4.0 mg g-1 DW) was nearly three times higher than that achieved in cultivation using 0.025% (v/v) antifoam. For continuous cell growth, the effect of inoculum age should also be considered when anti-foam is to be added. P medium strategy, without antifoam addition, not only promoted both growth (18 g 1-1) and AQ production (9.8 mg g-1 DW), but also resulted in lower foaming and wall-growth (below 30% level), and higher foaming reduction (30-40%).